Incidence Pattern and Outcome of Diseases in Patients Admitted in Coronary Care Unit in a Tertiary Care Hospital in Dhaka - A 3 Year Retrospective Study - Irfan, S M Rezaul; Habib, Samira Humaira; Sultana, Tasnia (Bangladesh Critical Care Journal, 2024)
Background: Cardiovascular disease (CVD) is the leading causes of death globally. Like other countries, CVD prevalence is also rising among the adults in Bangladesh. Most of the cardiac emergencies and acute ailments are preferably managed in a specially designed place of a hospital called Coronary Care Unit, which has better facilities of monitoring, care and support. In every day-to-day practice a proportion of diabetic patients need to admit in CCU for different life threatening crisis. For better understanding of such CVD prevalence scenario, we conducted this retrospective observational study. Aim of the Study: Our objective was to assess the pattern and incidence of CVD admitted in CCU with their outcomes among the population using the data from the record book. Methodology: This is a retrospective observational study carried out in the Coronary Care Unit (CCU) of BIRDEM Hospital Dhaka Bangladesh from 2017-2019. Total 1069 patients (861 were Diabetic and rest were non diabetic) who were admitted to the CCU of this Institute from 2017-2019 were studied and evaluated to see the pattern of cardiac emergencies in diabetic population. Results: Among 1069 patients, 57.2% were male and 42.8% were female. Majority (80.54%) of them were diabetic. Most of the patients belonged to age 50 years and above. Seven hundred and one (65.57%) patients were admitted due to Ischemic Heart Disease (IHD) in different forms. Among the Acute Coronary Syndrome, most prevalent one was NSTEMI (354). Among NSTEMI group, where 50.37% were male and 50.67% were female, 102 patients had Unstable Angina and 73 had STEMI. Eighty nine patients were admitted after intervention (PCI or CABG) and 61 patients had Ischemic Dilated Cardiomyopathy (IDCM) due to some complications. Four hundred and twenty patients admitted due to Heart Failure and 137 patients were admitted due to different forms of Shock. Cardiac function was assessed (by Teichholz method and Biplane Simpson's method) among the admitted patients and 57.31% of patients had moderate LV dysfunction, 29.26% had severe systolic dysfunction and remainder 13.43% found to have mild LV systolic dysfunction. Mean hospital stay was assessed and it was found to be gradually declining from 13.33 in 2017 to 9.23 in 2019 (p=0.041*). Outcome of the study population shows that 66% were transfer to general ward or cabin of the department of cardiology after initial stabilization, 17.3% were discharged directly from CCU, and 5.42% patients were transferred to other department after recovery. About 5.5% were become critically ill for which they need to transfer under care of ICU, 2.5% were transfer for intervention (to other institutes according to patient’s economical ability and preference for CABG, Pace maker implantation, PTCI etc.) and 3.3% patients were expired. Conclusion: In this study, incidence of IHD found higher than other cardiac diseases. NSTEMI is about three times more than Unstable Angina and about five times more prevalent than STEMI for the reason of admission in CCU. Diabetes Mellitus was found in majority of the admitted patients in CCU and the number of diabetic population is increasing which may also responsible for leading more coronary heart disease in our country in future. 88.7% of study population was shifted to general ward after initial stabilization after acute crisis, 2.5% required further cardiac intervention and 5.5% become critical and required ICU support. Only 3.3% of total population expired after all possible support. Bangladesh Crit Care J September 2024; 12 (2): 125-131